The Effect of Emotional Intelligence and Organizational Citizenship Behavior (OCB) on Nurse Performance at Mitra Sejati Hospital Medan - Riza Indriani; Irwansyah; Sienny; Niko Darlin Cibro (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of Emotional Intelligence and Organizational Citizenship Behavior (OCB) on Nurse Performance at Mitra Sejati General Hospital Medan. The population in this study amounted to 113 permanent nurses and used probability sampling as many as 88 respondents. Data processing using SPSS 22 for Windows. Based on the results of the study partially showed that there was a Positive and Significant influence of Emotional Intelligence Variables on Nurse Performance at Mitra Sejati General Hospital Medan by 37.2%. There is a Positive and Significant Influence of Organizational Citizenship Behavior (OCB) Variables on Nurse Performance at Mitra Sejati General Hospital Medan by 38%. Based on the results of the research with the Determination test, it shows that the Variables of Emotional Intelligence and Organizational Citizenship Behavior (OCB) simultaneously have an effect on Nurse Performance. This can be seen from the results of the Determination Coefficient Test which shows a value of 0.359 which means that Emotional Intelligence and Organizational Citizenship Behavior (OCB) affects the performance of nurses by 35.9% while the rest is influenced by other variables not examined in this study.